Peer Mentoring as a Restorative Justice Strategy for Youth Perpetrating Street Violence in the Special Region of Yogyakarta - Purwaningtyas, Mashita Phitaloka Fandia; Wijaya, Ina Yosia; Islahuddyn, Riski; Putri, Ayu Aishya; Setyawan, Stefanus Fajar; Puspandara, Viridhian Mangsah; Sasmito, Anggit Nur (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2024)
The Juvenile Social Protection and Rehabilitation Center (BPRSR) of Yogyakarta Special Region (DIY) handles juvenile street violence (klithih) oﬀenders but faces challenges in peer mentoring, a vital component of restorative justice. To enhance the skills of BPRSR staﬀ, the Youth Studies Centre (YouSure), in collaboration with the Centre for Public Mental Health (CPMH), organized a community service program in the form of a workshop series. The program aimed to strengthen staﬀ capabilities in identifying mental health problems, providing psychological ﬁrst aid, and oﬀering basic counseling. The training began with a pre-test to assess participants’ initial skills, followed by the training sessions, and concluded with a post-test. Results from the pre-test revealed a lack of understanding of the procedures for addressing mental health issues, while the post-test demonstrated a signiﬁcant improvement in both skills and knowledge. Despite the training’s eﬀectiveness, further followup is necessary to achieve a more comprehensive approach to restorative justice. Future training should be more in-depth and ongoing, addressing the identiﬁed gaps and supporting the practical application of these skills in adolescent rehabilitation at BPRSR.